Transboundary Cooperation and Global Governance for Inclusive Sustainable Development Contributions in Honour of Dirk Messner's 60th Birthday - Scholz, Imme; Busse, Lilian; Fues, Thomas (2022)
This book gathers renowned researchers and policymakers from all continents who have accompanied Dirk Messner's professional life in science and policy advice. Their articles and essays cover topics related to the ideational spheres and practice-oriented spaces which have consistently characterised Dirk Messner's career. These include steps at the national, regional or global level to effectively accelerate the shift towards planetary sustainability; measures to forge or strengthen cross-sectoral, transboundary, multi-actor alliances for sustainable transformation; and key elements of universal ethics and shared norms which foster transnational cooperation for the global common good. With contributions by Manish Bapna, Lilian Busse, Ani Dasgupta, J. Carlos Domínguez, Ottmar Edenhofer, Jörg Faust, Thomas Fues, Hans Haake, Medelina K. Hendytio, Ariel Macaspac Hernandez, Anna-Katharina Hornidge, Adolf Kloke-Lesch, Claus Leggewie, Siddharth Mallavarapu, Simon Maxwell, Dirk Meyer, Nebojsa Nakicenovic, Sabine Nallinger, Andrew Norton, Franz Nuscheler, Jiahua Pan Jürgen Renn, Enrique Saravia, Sabine Schlacke, Uwe Schneidewind, Imme Scholz, Svenja Schulze, Zita Sebesvari, Wolfgang Seidel, Elizabeth Sidiropoulos, Achim Steiner, Franziska Wehinger and Heidemarie Wieczorek-Zeul.